2018
DOI: 10.24326/asphc.2018.3.13
|View full text |Cite
|
Sign up to set email alerts
|

NECTAR PRODUCTION IN SEVERAL Campanula SPECIES (CAMPANULACEAE)

Abstract: The flowering, nectar production and sugar content were examined in 2012-2013 seasons for three Campanula species (C. persicifolia L., C. glomerata L., C. trachelium L.). The flowers of all studied Campanula spp. are distinctly protandrous; most of them opened between 10.00 and 14.00; only the flowers of C. glomerata continued the opening process until 16.00 (GMT + 2 h). The flower life-span differed between species and was the longest for C. persicifolia -ca. 5.5 days and lasted 3.0-3.5 days in C. glomerata a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In this study, the significant disparities in nectar and sugar production were noted between the cultivars. The variability in the nectar/ sugar amount produced in the flowers had been previously reported in many studies and related to the differences between species, cultivars, or even among individual flowers (Denisow et al, 2014a;Bożek et al, 2015;Strzałkowska-Abramek et al, 2018). P. serrulata 'Kanzan' and P. serrulata 'Amanogawa' differed in flower types, which, no doubt, impacted the quantity of the floral reward offered.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study, the significant disparities in nectar and sugar production were noted between the cultivars. The variability in the nectar/ sugar amount produced in the flowers had been previously reported in many studies and related to the differences between species, cultivars, or even among individual flowers (Denisow et al, 2014a;Bożek et al, 2015;Strzałkowska-Abramek et al, 2018). P. serrulata 'Kanzan' and P. serrulata 'Amanogawa' differed in flower types, which, no doubt, impacted the quantity of the floral reward offered.…”
Section: Discussionmentioning
confidence: 73%
“…As a major energetic food for pollinators, nectar plays an important ecological role in establishing plant-insect interactions (Strzałkowska-Abramek et al, 2016bNepi et al, 2018). Nectar traits (volume, sugar proportion, sugar concentration) vary considerably between species (Bożek et al, 2015;Strzałkowska-Abramek et al, 2018). Also environmental conditions impact considerably on nectar production and the sugar concentration (Petanidou and Smets, 1996;Nicolson and Thornburg, 2007;Denisow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Melliferous plants were introduced by Milecka et al [53] in the manor complex in Chociw (central Poland). The introduction of melliferous plants yields a strong visual effect, and appropriate species can be a reward base for insect pollinators [54][55][56][57][58][59], as recommended by the national pollinator strategy [60]. To supplement the pollinators food base of protected areas such the Felin Park, it is recommended that a "bee garden" with herbaceous reward plants (e.g., Brassica napus L. var.…”
Section: Discussionmentioning
confidence: 99%
“…The plants flower from June to August. The flowering stems are up to 70 cm high and bear on average 20-30 (up to 190) violetblue protandrous flowers arranged in clusters, which produce nectar (Denisow and Wrzesień, 2015;Strzałkowska-Abramek et al, 2018;Godefroid and Van Rossum, unpublished data). The species is characterized by a self-incompatible breeding system (Gadella, 1964).…”
Section: Study Speciesmentioning
confidence: 99%
“…These findings suggest extensive contemporary pollen flow within populations. Flowers of C. glomerata represent an important resource in nectar and pollen for many insects and so attract a variety of pollinators, such as bumble bees, solitary bees, honey bees and hoverflies (Albrecht et al, 2007;Denisow and Wrzesień, 2015;Strzałkowska-Abramek et al, 2018), which may favor extensive pollen flow across the whole population (Ghazoul, 2005;Van Rossum, 2010;DiLeo et al, 2018). High multiple paternity was also found in an isolated, but large population of the self-incompatible Arabidopsis halleri, with only 4% of offspring sharing the same father (Llaurens et al, 2008), while a value of 20% was found in a population of 96 flowering plants of the self-incompatible Centaurea corymbosa (Hardy et al, 2004).…”
Section: Extensive Contemporary Pollen Flow Within Populations But Li...mentioning
confidence: 99%